Contributions on the use of Bismuth as internal standard for lead determinations using icp-based techniques - Bechlin, Marcos A. [UNESP]; Ferreira, Edilene C. [UNESP]; Neto, José A. Gomes [UNESP]; Ramos, Juliano C.; Borges, Daniel L. G. (Sociedade Brasileira de Quimica (SBQ), 2015)
Bismuth was evaluated as internal standard for Pb determinations and showed usefulness to minimize variations due to changes in the experimental conditions of the inductively coupled plasma optical emission spectrometry (ICP OES), inductively coupled plasma mass spectrometry (ICP-MS) and electrothermal vaporization inductively coupled plasma mass spectrometry (ETV-ICP-MS). Thirty four samples were analyzed and the Pb contents obtained by ICP-MS and ETV-ICP-MS were in agreement at 95% confidence level. Plant, biological tissue and soil reference materials were also analyzed and the results were close to certified values upon the use of the internal standard. Recoveries for Pb spikes (ICP OES: 95-110%; ICP-MS: 95-106%; ETV-ICP-MS: 92-119%) were better than those obtained with external calibration (ICP OES: 56-91%; ICP-MS: 36-136%; ETV.ICP-MS: 5-123%). The relative standard deviations (n = 12) was improved from 1-9% to 0.2-6% (ICP OES), from 0.5-11% to 0.1-7% (ICP-MS) and from 0.4-7% to 0.1-4% (ETV.ICP.MS) by using external and internal standard calibrations, respectively.
Keywords: Bi internal standard; ETV-ICP-MS; ICP OES; ICP-MS; Lead determination